Standardization catch-up strategy of latecomer enterprises: a longitudinal case of Huawei - Wei Yang; Yurong Zhang (Humanities & Social Sciences Communications)
Abstract The existing theoretical framework fails to explain the behavioral mechanisms employed by latecomer enterprises in their pursuit of standardization catch-up. In order to address this gap, we conducted a comprehensive and structured case study on Huawei’s standardization strategy. Using both deductive and inductive approaches, the findings from our research reveal Huawei’s ‘pyramid standardization strategy’ consisting of four distinct stages: following (1987–2002), defense (2003–2008), breakthrough (2009–2015), and sharing (2016–present). Drawing from the theoretical framework of academic literature on ‘catch-up in standardization’, we propose a ‘standardization catch-up model’ that incorporates three crucial elements: a top-down behavioral foundation, middle-up essential supporting components, and bottom-up culture and values. Furthermore, we identified five key propositions from the Huawei case, which emphasize the importance of R&D investment, low-cost engineers, professional teams, relations with international standards organizations, and open innovation as driving factors. By shedding light on the role of internal capabilities, patent-based innovation, and organizational culture, our research significantly contributes to the understanding of catch-up through standardization strategy.